2021
DOI: 10.3389/fpls.2021.657773
|View full text |Cite
|
Sign up to set email alerts
|

Seed Shattering: A Trait of Evolutionary Importance in Plants

Abstract: Seed shattering refers to the natural shedding of seeds when they ripe, a phenomenon typically observed in wild and weedy plant species. The timing and extent of this phenomenon varies considerably among plant species. Seed shattering is primarily a genetically controlled trait; however, it is significantly influenced by environmental conditions, management practices and their interactions, especially in agro-ecosystems. This trait is undesirable in domesticated crops where consistent efforts have been made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 176 publications
0
42
0
Order By: Relevance
“…Now that HWSC techniques are available, there has recently been a concerted research effort to quantify weed seed retention in order to identify the potential for HWSC to target the dominant, and frequently herbicide-resistant, weed species in several of the world's major cropping systems. These studies (see reviews by Walsh et al 2018b;Maity et al 2021) have investigated seed retention at crop maturity of >30 weed species prominent in these grain production systems. Importantly, these studies have identified the opportunity for HWSC to target significant proportions (50-99%) of the seed production of the particularly damaging weeds Palmer amaranth (Amaranthus palmeri), water hemp (Amaranthus tuberculatus), annual ragweed (Ambrosia artemisiifolia L.), Italian ryegrass (Lolium perenne subsp.…”
Section: Identifying the Potential Of Hwsc In Global Cropping Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now that HWSC techniques are available, there has recently been a concerted research effort to quantify weed seed retention in order to identify the potential for HWSC to target the dominant, and frequently herbicide-resistant, weed species in several of the world's major cropping systems. These studies (see reviews by Walsh et al 2018b;Maity et al 2021) have investigated seed retention at crop maturity of >30 weed species prominent in these grain production systems. Importantly, these studies have identified the opportunity for HWSC to target significant proportions (50-99%) of the seed production of the particularly damaging weeds Palmer amaranth (Amaranthus palmeri), water hemp (Amaranthus tuberculatus), annual ragweed (Ambrosia artemisiifolia L.), Italian ryegrass (Lolium perenne subsp.…”
Section: Identifying the Potential Of Hwsc In Global Cropping Systemsmentioning
confidence: 99%
“…HWSC treatments will most likely continue to be used in Australian grain production systems because of the unique timing of this weed control approach, notwithstanding that there is species-specific, incomplete weed seed retention at crop maturity. With the degree of weed seed retention influenced by genetic and environmental factors (Walsh and Powles 2014;Walsh et al 2018a;Borger et al 2020;Maity et al 2021), HWSC cannot be solely relied on for weed control, but must be viewed as a supplemental weed control practice. Similarly, because HWSC treatments have an end-of-season timing, their use will continue to be supported by earlier, in-crop weed control treatments (usually herbicides) to minimise weed interference during the growing season.…”
Section: Securing the Long-term Use Of Hwsc Systemsmentioning
confidence: 99%
“…A close examination of the prevailing weather conditions for a 3-wk period before wheat harvest in the two study years revealed that 2018 was relatively warmer and drier (daily average temperature 26 C, relative humidity 73%) with fewer rainfall events (daily average precipitation 0.5 mm), compared to 2019 with 23 C daily average temperature, 83% relative humidity, and 2.5 mm daily average precipitation [weather data was obtained from a nearby weather station located within the Texas A&M research farm (http://afs102.tamu.edu/)]. High seed shattering under warm and dry weather conditions was documented by several studies (e.g., Gan et al 2008;Maity et al 2021c;Shirtliffe et al 2000;Tiwari and Bhatnagar 1989).…”
Section: Spike Density Fecundity and Seed Retentionmentioning
confidence: 99%
“…Studies have shown that the frying rate of French croissant pods at low temperature and high humidity is significantly lower than that at high temperature and low humidity [41]. Subsequently, Cavines et al, successively proposed that relative humidity is an important environmental factor affecting soybean seed shattering [42,43]; in addition, Zhang et al [34], not only verified the above views, but also put forward that there is no obvious correlation between the seed shattering rate and the length of sunshine time and the average daily temperature. Yang researched that seed shattering occurred when the moisture content of beans and seed shattering were lower than 25% and 15%, respectively, indicating that the water content of soybeans is also closely related to seed shattering and also proposed that the spatial distribution of pods in identical soybean does not significantly link [44].…”
Section: Environmental Factors Of Seed Shatteringmentioning
confidence: 99%